Scientifically based research in a post-truth era - Van Cleave, Jessica (Education Policy Analysis Archives, 2018)
In this article, I explore the tension between the current political context in which science needs defending against anti-intellectualism and outright assaults on evidence as a means of decision-making on the one hand and the overzealous scientism that can result from backlash against a perceived lack of rigor in various forms of inquiry. To do so, I return to the emergence of the discourse of scientifically based research (SBR) in education and the debates surrounding it (2002-2013), which have implications for how and why educational researchers would advocate for science and what that advocacy might do. Specifically, I argue that we must have a science that does not allow alternative facts and politically expedient truth claims while still allowing science to be flexible, responsive, and theoretically informed. I conclude by advocating for theoretically informed activism and non-innocent science.